1998
DOI: 10.1136/adc.78.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolites in cystic fibrosis lung disease

Abstract: Although the activity of nitric oxide (NO) synthases are increased in lung tissue of patients with cystic fibrosis, the concentrations of nasal and exhaled NO have recently been found to be decreased in cystic fibrosis. This could either be due to reduced NO formation or metabolism of NO within airway fluids. In this study, the stable NO metabolites, nitrate and nitrite, were determined in the saliva and sputum of 18 stable cystic fibrosis patients, 21 cystic fibrosis patients during a pulmonary exacerbation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
130
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 27 publications
8
130
2
1
Order By: Relevance
“…For example, synergistic and antagonistic behavior between different CF pathogens has been described (Duan et al, 2003;Harrison, 2007;Sibley et al, 2008;Mitchell et al, 2010;Yang et al, 2011;Venkataraman et al, 2014), and the microbial community has been proposed to contain stable and disturbed states, much like those in classical ecology (Conrad et al, 2012). Known chemical characteristics of the CF lung include lowered pH (Tate et al, 2002;Pezzulo et al, 2012), low oxygen tensions (Worlitzsch et al, 2002) and high levels of amino acids, nitrate, iron and phenazines (Grasemann et al, 1998;Jones et al, 2000;Palmer et al, 2007;Ghio et al, 2012;Hunter et al, 2012). In the environment, microbial communities are known to stratify based on oxygen and other chemical gradients (Fenchel and Finlay, 2008;Morris and Schmidt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, synergistic and antagonistic behavior between different CF pathogens has been described (Duan et al, 2003;Harrison, 2007;Sibley et al, 2008;Mitchell et al, 2010;Yang et al, 2011;Venkataraman et al, 2014), and the microbial community has been proposed to contain stable and disturbed states, much like those in classical ecology (Conrad et al, 2012). Known chemical characteristics of the CF lung include lowered pH (Tate et al, 2002;Pezzulo et al, 2012), low oxygen tensions (Worlitzsch et al, 2002) and high levels of amino acids, nitrate, iron and phenazines (Grasemann et al, 1998;Jones et al, 2000;Palmer et al, 2007;Ghio et al, 2012;Hunter et al, 2012). In the environment, microbial communities are known to stratify based on oxygen and other chemical gradients (Fenchel and Finlay, 2008;Morris and Schmidt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent inflammation and repeated cycles of infection are present in CF lungs, resulting in progressive lung damage and pulmonary fibrosis (25). Even in stable patients, chronic airway inflammation is present, as reflected by high airway fluid concentrations of proinflammatory cytokines (26). Analysis of BAL fluid has shown a 1.000-fold increase in the number of neutrophils from the lungs of patients with CF compared with controls (27).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our laboratory reported that H 2 O 2 -producing oral commensal streptococci can inhibit P. aeruginosa in a nitritedependent manner through the production of reactive (Scoffield & Wu, 2015). Nitrite is readily available within the oral cavity and CF lung, and is a byproduct of denitrifying bacteria (Grasemann et al, 1998;Hezel & Weitzberg, 2015). Nitrite reductase is one of several enzymes unique to the denitrification pathway of P. aeruginosa and is responsible for catalysing the reduction of nitrite to nitric oxide.…”
Section: Introductionmentioning
confidence: 99%